2021
DOI: 10.1101/2021.05.27.446071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A homing suppression gene drive with multiplexed gRNAs maintains high drive conversion efficiency and avoids functional resistance alleles

Abstract: Gene drives are engineered alleles that can bias inheritance in their favor, allowing them to spread throughout a population. They could potentially be used to modify or suppress pest populations, such as mosquitoes that spread diseases. CRISPR/Cas9 homing drives, which copy themselves by homology-directed repair in drive/wild-type heterozygotes, are a powerful form of gene drive, but they are vulnerable to resistance alleles that preserve the function of their target gene. Such resistance alleles can prevent … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 93 publications
(236 reference statements)
1
32
0
Order By: Relevance
“…Fortunately, we found that the strategy of targeting a haplosufficient but essential female-specific gene with a homing drive was still able to achieve high genetic load (and though we modelled a female fertility gene, results would be broadly similar with a female viability gene). This type of gene drive has been well studied, with the latest drives even circumventing functional resistance alleles by careful target site selection 5 or multiplexed gRNAs 42 . Because haplodiploid drives are somewhat more vulnerable to such functional resistance alleles, both methods would likely also be needed to avoid functional resistance in large, natural haplodiploid populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, we found that the strategy of targeting a haplosufficient but essential female-specific gene with a homing drive was still able to achieve high genetic load (and though we modelled a female fertility gene, results would be broadly similar with a female viability gene). This type of gene drive has been well studied, with the latest drives even circumventing functional resistance alleles by careful target site selection 5 or multiplexed gRNAs 42 . Because haplodiploid drives are somewhat more vulnerable to such functional resistance alleles, both methods would likely also be needed to avoid functional resistance in large, natural haplodiploid populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study indicates that homing suppression drives in haplodiploids would need to keep somatic activity and embryo resistance allele formation even lower than in diploid drives to be effective. Though a rigorous requirement, there is still some flexibility in the specific values, and previously constructed drives have already achieved low enough somatic activity in flies 42 and embryo resistance in mosquitoes 5 . Surprisingly, we found that in continuous space models, female fertility homing suppression drives perform nearly as well in haplodiploid species as in diploids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 10 mM Tris-HCl, 100 μM EDTA solution at pH 8.5 was used for the injection. Both lines containing split homing modification 21 and suppression 47 drives were generated in previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Details of this approach and its application to cage population data were previously described 48 . The fitness parameters for both homing lines used here have been previously estimated 21,47 . For the TARE line, we estimated the viability, female fecundity, and male mating success parameters and the effective population size using a model that assumes a co-dominant, multiplicative fitness effect of the TARE allele (heterozygotes were assigned fitness equal to the square root of homozygotes).…”
Section: Methodsmentioning
confidence: 99%